Physical literacy among chinese elementary school students: the mediating role of physical knowledge and physical competency - Li Mengyu; Wang Yuxing; Zan Ziqing; Liu Lizhu; You Lili (BMC Public Health)
Abstract Background Physical literacy (PL) is pivotal for improving sedentary behaviors, enhancing intrinsic motivation for physical activity, and supporting the growth and development of adolescents. This study aims to measure the current situation and internal pathway of PL among Chinese elementary school students. Methods This study was conducted from June to July 2022 and used multistage cluster sampling to select the study subjects. Questionnaire measurements were used to report the levels of PL among elementary school students and to explain the internal association among the various PL dimensions. Results The average PL score among primary school students was 63.46 points. The qualification rates for PL in the three academic stages were 76.35%, 73.45%, and 59.17%, respectively. The study included 1499 boys (49.72%) and 1516 girls (50.28%). The average age was 9.04 ± 1.60 years. Physical motivation, physical competency and physical participation were positively associated with PL in each grade. Physical competency mediated the association between physical motivation and physical participation, explaining 56.40% of the effect. Conclusion The qualification rates for PL in grades 5–6 was lower than those of students in grades 3–4 and grades 1–2. Physical competency explained 56.40% of the association between physical motivation and physical participation. Clinical trial number Not applicable